Functional Interaction between PomA and PomB, the Na(+)-Driven Flagellar Motor Components of Vibrio alginolyticus - Yorimitsu, Tomohiro (American Society for Microbiology, 1999)
Four proteins, PomA, PomB, MotX, and MotY, appear to be involved in force generation of the sodium-driven polar flagella of Vibrio alginolyticus. Among these, PomA and PomB seem to be associated and to form a sodium channel. By using antipeptide antibodies against PomA or PomB, we carried out immunoprecipitation to verify whether these proteins form a complex and examined the in vivo stabilities of PomA and PomB. As a result, we could demonstrate that PomA and PomB functionally interact with each other.